1972
DOI: 10.1136/adc.47.255.754
|View full text |Cite
|
Sign up to set email alerts
|

Response to Glucagon in Small-for-dates Hypoglycaemic and Non-hypoglycaemic Newborn Infants

Abstract: Le Dune, M. A. (1972). Archives of Disease in Childhood, 47, 754. Response to glucagon in small-for-dates hypoglycaemic and non-hypoglycaemic newborn infants. 32 glucagon tests with insulin studies have been performed in hypoglycaemic and non-hypoglycaemic small-for-dates infants. The results suggest that glycogen depletion is an important factor in neonatal hypoglycaemia, and varies with the degree of hypoglycaemia. Hyperinsulinism was found in a proportion of hypoglycaemic infants, though there did not appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

1975
1975
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…Previous studies have been limited in actual number, and confined predominantly to term infants, particularly those who were growth restricted. [18][19][20][21] In a group of 11 infants with comparable corrected gestational age to our group of infants at first test (36 weeks gestation) but at a median age of 24 hours postnatal age, a different pattern of response was evident to our infants, and only one infant failed to increase their concentration of blood glucose >1 mmol/l in response to glucagon. 22 Glucagon stimulation in type 1a glycogen storage disease results in a typically flattened glucose response in combination with an exaggerated lactate response.…”
Section: Discussionmentioning
confidence: 47%
“…Previous studies have been limited in actual number, and confined predominantly to term infants, particularly those who were growth restricted. [18][19][20][21] In a group of 11 infants with comparable corrected gestational age to our group of infants at first test (36 weeks gestation) but at a median age of 24 hours postnatal age, a different pattern of response was evident to our infants, and only one infant failed to increase their concentration of blood glucose >1 mmol/l in response to glucagon. 22 Glucagon stimulation in type 1a glycogen storage disease results in a typically flattened glucose response in combination with an exaggerated lactate response.…”
Section: Discussionmentioning
confidence: 47%
“…It is suggested that further attempts be made to correlate etiologic events with meta bolic responses in clinical intrauterine growth retardation. This may help to better define the nature of those rare, but clearly described, growth-retarded and hypoglycemic neonates who appear to suffer from hyperinsulinemia (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…The question of why the infant with reduced, but not absent, energy Substrates becomes hypoglycemia early in life is challenging and opens several areas of speculation. These infants produce their own regulating hormones early in fetal life and there is no transfer of glucagon [19], insulin [20] or growth hormone [21] across the placenta; yet several investigators [22,23] have documented impaired gluconeogenesis in the SGA or dysmature rat and human. NITZAN [24] produced growth retardation by ligating the uterine hörn on the seventeenth day of gestation and found the liver slices from the dysmature fetal rats incorporated labelled alanine into glucose and phospholipids less well than the control slices.…”
Section: Infants With Reduced Available Substratementioning
confidence: 99%
“…It is especially impoitant to supply early caloric and protein support to the infant who has had placental dysfunction, is postmature or who has evidence of intrauterine wasting of both muscle and fat tissue. These infants are more prone to have convulsions with hypoglycemia with residual brain damage; a fact possibly felated to a more mature central nervous System [26], It is important not to administer glucagon alone in the SGA infant äs several investigatofs have demonstfated that little or no rise in blood glucose may occur with glucagon infusion in the face of marked hypoglycemia [5,22], Neither epinephrine nor steroids have been shown to be rapidly effective in this group.…”
Section: Infants With Reduced Available Substratementioning
confidence: 99%